2014
DOI: 10.3109/07435800.2014.913614
|View full text |Cite
|
Sign up to set email alerts
|

Associations of small dense low-density lipoprotein and adiponectin with complications of type 2 diabetes

Abstract: Our data suggest that decreased levels of adiponectin might be associated with developing complications of diabetes. This study did not provide any supportive results for the association of increased sd-LDL concentrations with CVD; neither for its association with other complications of diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…While both diastolic and systolic blood pressure are included in metabolic syndrome, still we could not observe significant differences for various lipid markers among hypertensive and nonhypertensive patients which is in line with the findings of Esteghamati et al [ 27 ]. However, we found the ratio between sdLDLc/lbLDLc to have weak correlation with systolic and diastolic blood pressures, which indicates that slight derangements in lipid metabolism do develop in subjects having raised blood pressures [ 28 , 29 ].…”
Section: Discussionsupporting
confidence: 92%
“…While both diastolic and systolic blood pressure are included in metabolic syndrome, still we could not observe significant differences for various lipid markers among hypertensive and nonhypertensive patients which is in line with the findings of Esteghamati et al [ 27 ]. However, we found the ratio between sdLDLc/lbLDLc to have weak correlation with systolic and diastolic blood pressures, which indicates that slight derangements in lipid metabolism do develop in subjects having raised blood pressures [ 28 , 29 ].…”
Section: Discussionsupporting
confidence: 92%
“…Several studies have demonstrated that serum adiponectin level is inversely associated with obesity 26,27 and insulin resistance [28][29][30] . Hypoadiponectemia is significantly related to type 2 diabetes 31 , and independently associated with the MS 12,32,33 . These findings are in agreement with those of the present study which revealed that circulating adiponectin levels were inversely associated with the presence of MS.…”
Section: Discussionmentioning
confidence: 98%